The five-jump test for distance as a field test to assess lower limb explosive power in soccer players - Chamari, K.; Chaouachi, A.; Hambli, M.; Kaouech, F.; Wisloff, U.; Castagna, C. (The Journal of Strength and Conditioning Research, 2008)
The 5-jump test (5JT) was proposed to evaluate lower limb explosive power of athletes competing in various disciplines. Although 5JT performance is usually expressed in absolute terms as the overall distance covered (i.e., in meters), subject size can play a significant role in the performance. The aims of the present study were to test the relationship of 5JT absolute performance with laboratory tests for explosive power and to develop performance notations useful to improve the diagnostic value of 5JT. Fifteen elite soccer players, members of the Under-23 Tunisian national team, were tested for 5JT, force platform vertical jumping (squat jump [SJ] and arm-aided countermovement jump [Arm-CMJ]), and concentric isokinetic leg extension/flexion (90°/s and 240°/s). 5JT performance was expressed in absolute terms (meters), relative to leg length (5JT-relative) and with body mass-dependent notations (Body mass × 5JT, 5JT-body mass). 5JT performance was significantly correlated with SJ height and scaled (W·kg-0.67) peak power (0.72 and 0.77, respectively, p < 0.01). 5JT-relative values were significantly related to SJ and Arm-CMJ height (0.61 and 0.71, respectively, p < 0.05) and scaled peak power (0.57 and 0.59, respectively, p < 0.05). 5JT-body mass revealed significantly related of SJ (0.82, p < 0.0001) and Arm-CMJ peak power (0.54, p < 0.05) and to SJ and Arm-CMJ peak force (0.67 and 0.65, respectively p < 0.05). 5JT-relative and 5JT-body mass correlated significantly with knee extensors 240°/s (0.60, p < 0.05) and knee flexors 90°/s (0.67, p < 0.01) isokinetic acceleration time, respectively. The results of this study suggest that the 5JT may be regarded as an explosive strength diagnostic tool under field conditions in elite soccer players. The use of performance notation accounting for body size differences may improve the diagnostic ability of 5JT.